STRATEGI KEMANDIRIAN EKONOMI PONDOK PESANTREN DI MASA PANDEMI COVID-19 - Akhmad Syahid (Jurnal Dakwah Tabligh, 2021)
Pondok Pesantren is the oldest institution in the field of Islamic proselytizing as well as education in Indonesia. Its existence has proven to have made a major contribution to the history of the Indonesian independence struggle. Historically, the establishment of Islamic boarding schools was initiated and practiced by individuals (Kyai) and some were from an association or organization. In 2019, a virus emerged that seriously endangered human life in the Wuhan region of China. In early 2020, the dangerous virus spread to Indonesia and was better known as Corona Virus Disease (Covid-19). The spread of Covid-19 has greatly impacted various aspects of life, including Islamic boarding schools. Pondok Pesantren is very much feeling the impact, one of which is in the economic sector, where the learning process must continue while the income/income from student guardians decreases drastically. This research used qualitative research methods, using a phenomenological approach. The research place is the Al-Amin Islamic Boarding School in Central Lampung, with a data collection method by means of interviews, observations, and documentation. The results of this study show that the impact of Covid-19 greatly affects the operation of the Islamic Boarding School, even so, the Al-Amin Islamic Boarding School in Central Lampung remains responsible by continuing to carry out guidance and learning to the students. To support the operational costs of the Islamic Boarding School, independent efforts were made to improve economies, such as by opening confections, catfish and carp farming, laundry, and canteens.